Relationship of intestinal histology with the resistance to Trichostrongylus colubriformis infection in three breeds of sheep Associação entre a resposta celular no intestino e a resistência à infecção por Trichostrongylus colubriformis em três raças de ovinos - Alessandro F.T. Amarante; Raquel A. Rocha; Patrizia A. Bricarello (Pesquisa Veterinária Brasileira, 2007)
The study was carried out to evaluate the relationship of inflammatory intestinal cells with the resistance to Trichostrongylus colubriformis infections in three breeds of sheep (Santa Ines, Suffolk and Ile de France), naturally infected. Mast cells, eosinophils, and globule leucocytes were enumerated in intestinal mucosa. Histamine concentration was estimated in intestinal tissue samples and the length of male and female specimens were determined. The three breeds of sheep showed similar cellular response in the small intestine mucosa (P>0.05). There was extensive variation among sheep in the parasitological and inflammatory cell variables, even in lambs of the same breed. In general, animals presenting less inflammatory cells had a larger worm burden, higher fecal egg counts, and larger T. colubriformis worms. The inflammatory cells possibly impaired the parasite's establishment, development, and survival. Avaliaram-se a associação entre o número de células inflamatórias no intestino delgado e a resistência à infecção por Trichostrongylus colubriformis em ovinos de três raças (Santa Inês, Suffolk e Ile de France), naturalmente infectados. Mastócitos, eosinófilos e leucócitos globulares foram quantificados na mucosa intestinal. A concentração de histamina foi estimada em amostras teciduais do intestino, bem como foi determinado o comprimento de machos e fêmeas de T. colubriformis. A resposta celular foi similar na mucosa intestinal das três raças ovinas (P>0,05). Houve grande variação entre os ovinos em relação aos resultados parasitológicos e celulares, mesmo nos animais de mesma raça. Em geral, os animais que apresentaram número menor de células inflamatórias tiveram cargas parasitárias maiores, contagens de ovos por grama de fezes mais altas e exemplares de T. colubriformis maiores. Os resultados indicaram que mastócitos, eosinófilos e leucócitos globulares prejudicaram o estabelecimento, o desenvolvimento e a sobrevivência dos parasitas.